Front Cover: Host–Guest Complexation Using Pillar[5]arene Crystals: Crystal‐Structure Dependent Uptake, Release, and Molecular Dynamics of an Alkane Guest (Chem. Eur. J. 10/2019). Issue 10 (25th January 2019) - Ogoshi, Tomoki; Hamada, Yukie; Sueto, Ryuta; Sakata, Yoko; Akine, Shigehisa; Moeljadi, Adhitya Mangala Putra; Hirao, Hajime; Kakuta, Takahiro; Yamagishi, Tada‐aki; Mizuno, Motohiro
Abstract : Host–guest complexation has been mainly investigated in solution; therefore, revealing crystal‐state host–guest complexation is a challenging task. This work reports the unique features of crystal‐state host–guest complexation; that is, how guest molecules access the host assembled structures and the dynamics of guest molecules encapsulated in crystals. More information can be found in the Full Paper by T. Ogoshi et al. onpage 2497 .